If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 5x + 13 Reorder the terms: 0 = 13 + 5x Solving 0 = 13 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 0 + -5x = 13 + 5x + -5x Remove the zero: -5x = 13 + 5x + -5x Combine like terms: 5x + -5x = 0 -5x = 13 + 0 -5x = 13 Divide each side by '-5'. x = -2.6 Simplifying x = -2.6
| 5x+2x+36=180 | | 6(0)2-4=0 | | 3x^2+24x+32=0 | | 4p-14+3p=51 | | 0.75ml=15 | | ln(x)+ln(x-3)=ln(10) | | 9x^2+30x=29 | | 54=w/3 | | (y^2+2)(5y+7)= | | 6x-2=.02 | | 2x+3x+13=90 | | 0.5(x-1)=2(x+5) | | w-4w= | | F(x)=9x-13 | | 3(5+3x)-2=23 | | 10y+10-3y=-11 | | -3x+9=4x+12 | | 4(p+6q-10)= | | 5r^3-10r^2=0 | | -16t^2+100t+5=0 | | C+(61)=-97 | | 40x+15y=505 | | (-a^2+1)-(a^2-2)+(5a^2-4a+8)= | | 100x=20 | | r/4-10=-6 | | sqrt(2−3x)/sqrt(5x)=3 | | 2x+12x+8=15 | | 4t^2+12t=12 | | 3/4-x/2=3/8 | | y=.6x-3 | | C+(-16)=-97 | | 3y/2 |